A tunable single CDTRA based current and transimpedance mode wheatstone bridge interface with software assisted linearization - Cimen, Sibel; Ayten, Umut Engin (ELSEVIER GMBH, 2026)
This paper introduces a novel current-mode Wheatstone bridge (CMWB) topology utilizing a single Current Differencing Transresistance Amplifier (CDTRA) as the active building block and four resistors. The proposed design distinguishes itself by providing simultaneous current and voltage outputs, featuring high-impedance for the current output and low-impedance for the voltage output, which facilitates easy integration with subsequent circuit stages. Furthermore, the configuration features electronic tunability, allowing the gain to be controlled via the I bias current through the transresistance r m parameter of the CDTRA. In dual-sensor applications, the proposed circuit ensures a linear output variation for both current and voltage with respect to sensor resistance changes. To support accurate single-sensor readout under realistic digitization conditions, a low-order digital calibration/linearization stage is presented and demonstrated for PT100 temperature sensing under noise and ADC quantization effects. The performance and feasibility of the design are verified through both PSPICE simulations and experimental measurements.
Keywords: Wheatstone bridge; Current mode; Transimpedance mode; Current differencing Transresistance amplifier; (CDTRA); Resistive sensors; Temperature sensing; AMPLIFIER; Engineering; Telecommunications